Use of aceclofenac for the treatment of chronic pain in rheumatology - Yu. A. Olyunin (Современная ревматология)
The high anti-inflammatory activity and pronounced analgesic effect of nonsteroidal anti-inflammatory drugs ((NSAIDs) allow successful treatment for pain syndrome associated with many diseases, primarily rheumatic diseases. NSAIDs are the main agents used to relieve pain in osteoarthritis, lower back pain, and  periarticular soft tissue diseases. They are also an essential  component of combination pharmacotherapy for chronic arthritis.  The therapeutic effect of NSAIDs is determined by the suppressed  activity of the cyclooxygenase (COX) isoenzymes COX- 1 and COX-2. The widely use of NSAIDs in clinical practice is considerably limited by the risk of adverse reactions (ARs) in the gastrointestinal tract  (GIT), which are characteristic for this class of drugs. Medications  that are able to selectively inhibit the activity of COX-2 while  maintaining that of COX-1 less rarely cause ARs in GIT. This selective effect is produced by aceclofenac. A number of clinical trials have demonstrated the high efficacy of this drug in treating various  locomotor diseases. The drug has been also noted to be well  tolerated: the risk for aceclofenac- induced ARs in GIT is  substantially lower than that due to the use of the majority of other NSAIDs.